Evaluation value of SWI with 7.0T MRI for choroid plexus vein imaging - ZHEN Zhiming; XIAO Shilei; LIU Chen (陆军军医大学学报, 2023)
Objective To explore the quality evaluation value of 7.0T ultra-high field MRI-SWI sequence in choroid plexus (CP) vein. Methods Fifty healthy individuals were recruited in our hospital from May to August 2022. All of them received 7.0T and 3.0T magnetic susceptibility weighted imaging (SWI) on the same day. The subjective index Likert5 subscale was used to evaluate the overall image quality and CP calcification display quality, and visual quartet was used to evaluate the CP vein display quality. The contrast-to-noise ratio (CNR) of the cerebrospinal fluid to CP was calculated by objective index. Mann-Whitney U test was used for intergroup comparison. Results There were 42 subjects finally included in the study. Likert5 scores of overall image quality showed that the images from the 7.0T group were superior to those of the 3.0T group [5 (5, 5) vs 4 (3, 4); P < 0.001]. CP vein scores of visual quartering showed the 7.0T group was better than the 3.0T group [0 (0, 1) vs 3 (2, 3); P < 0.001]. Among the 42 subjects, 31 had CP calcification. and the Likert5 scores of calcification showed that the 7.0T group was greater than the 3.0T group [5 (4, 5) vs 3 (3, 4); P < 0.001]. The contrast-to-noise ratio (CNR) value of 7.0T MRI group was significantly higher than that of the 3.0T MRI group (12.76±4.00 vs -2.13±12.75; P < 0.001). Conclusion 7.0T MRI ultra-high field strength SWI sequences is superior to 3.0T MRI for evaluating the quality of choroid plexus vein imaging.